2022
DOI: 10.1080/0886022x.2022.2097923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine for prevention of acute kidney injury after cardiac surgery: an updated systematic review and meta-analysis

Abstract: Background Acute kidney injury (AKI) is a serious complication related to cardiac surgery. Several studies have been conducted to investigate the effect of dexmedetomidine administration on AKI prevention. Objective To assess if dexmedetomidine is associated with a protective effect of renal function after cardiac surgery. And the aim of conducting this meta-analysis is to summarize the literature and determine the clinical utility of dexmedetomidine administration in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…A recent updated systematic review and meta-analysis of 16 studies involving 2148 patients revealed that dexmedetomidine administration may prevent AKI and postoperative delirium after cardiac surgery. This meta-analysis also suggests that dexmedetomidine may reduce the length of stay in the intensive care unit [175]. Likewise, dexmedetomidine administration was associated with improvements in renal function recovery and in-hospital survival in critically ill patients with septic AKI [79].…”
Section: Sympatholyticsmentioning
confidence: 65%
“…A recent updated systematic review and meta-analysis of 16 studies involving 2148 patients revealed that dexmedetomidine administration may prevent AKI and postoperative delirium after cardiac surgery. This meta-analysis also suggests that dexmedetomidine may reduce the length of stay in the intensive care unit [175]. Likewise, dexmedetomidine administration was associated with improvements in renal function recovery and in-hospital survival in critically ill patients with septic AKI [79].…”
Section: Sympatholyticsmentioning
confidence: 65%
“…Han, Y et al found that intraoperative application of a loading dose of dexamethasone combined with propofol during maintenance of anesthesia reduced heart rate and thus oxygen consumption by cardiac myocytes[28]. In addition, several studies have reported that perioperative use of dexmedetomidine reduced the duration of intensive care and tracheal intubation and the incidence of short-term mortality after cardiac surgery in adults [11,12,29,30]. In our study, we also found that dexmedetomidine as an anesthetic adjuvant was associated with a reduced incidence of major postoperative complications and a reduced cicu stay.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dexmedetomidine was shown to be advantageous for the protection of kidney function in cardiac surgery patients. 105,108,112 Current practices may combine epidural and general anesthesia for better intra-and postoperative pain control with simultaneous opioid sparing. Epidural anesthesia, introduced after the induction of narcosis, resulted in not raised, but decreased serum vasopressin levels when low-pressure pneumoperitoneum (7-9 mmHg) was applied during laparoscopic cholecystectomy.…”
Section: Alternative Techniques For Laparoscopymentioning
confidence: 99%
“…Moreover, dexmedetomidine was shown to be advantageous for the protection of kidney function in cardiac surgery patients. 105,108,112…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%